The geomorphology of Svínafellsjökull and Virkisjökull-Falljökull glacier forelands, southeast Iceland - Everest, Jeremy D; Bradwell, Tom; Jones, Lee; Hughes, Leanne (Journal of Maps, 2017)
A detailed, 1:10,500-scale, surficial geology and glacial geomorphology map of Svínafellsjökull and Virkisjökull-Falljökull glacier forelands in southeast Iceland depicts the landsystem imprint of Holocene glacier fluctuations, volcanogenic outburst floods and recent (post-1990) climate-induced rapid ice-front retreat. The map is based on field survey data in combination with 2012 airborne LiDAR data, 2009–2012 terrestrial LiDAR data and 2007 colour aerial photography. The base digital elevation model (DEM) is compiled from an ice-cap wide airborne LiDAR dataset. The mapped glacial landforms are dominated by sequences of recessional moraines laid down in the mid-Holocene, the Little Ice Age, and the last ∼100 years; the state of landform preservation generally decreasing with age. Interspersed with glaciofluvial sedimentation associated with typical ice-marginal retreat sequences is key geomorphological evidence of high-magnitude volcanogenic outburst floods (jökulhlaups) associated with the eruptions of Öraefajökull in 1362 and 1727 CE. Ice-front retreat has accelerated since c.2005 leaving a rapidly evolving buried-ice landscape in front of Virkisjökull-Falljökull – including an ice-cored esker, a large ice-floored (supraglacial) lake, and numerous actively forming kettle holes and ice caverns. This map could act as a ‘reference frame’ for geomorphologists studying the temporal evolution of glacial landform-sediment assemblages undergoing rapid change.